PENGARUH STRUKTUR MODAL TERHADAP LABA PER LEMBAR SAHAM PADA PT.XL AXIATA BANDUNG INDONESIA, TBK - Efi Fitriani (JURISMA : Jurnal Riset Bisnis & Manajemen, 2015)
PT XL AXIATA,Ltd Bandung (XL) Indonesia is one of the state Owned Enterprises (SOEs), Which Provides PT XL AXIATA services and the largest network in indonesia, Located on Jl Japati No. 1 Bandung. To attract Investors, Indonesian PT XL AXIATA, Ltd Bandung (XL) should pay attention to Earnings Per Share, because it indicates the level of corporate welfare.The purpose of this study is to determine the condition of the capital structure, to know the rate of changes of earnings per share, and to know the influence of capital structure to earnings per share at indonesian PT XL AXIATA, Ltd Bandung (XL).This research uses descriptive method with quantitative appriach. Data needed for this research is from financial statements in the form of balance sheets and income statements of publicly listed companies of 17 years.Results of this study show that capital structure has negative influence on earnings per share, but not significant.